Jejak Sejarah Peradaban Islam di Bengkulu melalui Tradisi Tabot: Perspektif Sejarah dan Budaya - Fransiska, Weta (Pakis Journal Institute, 2025)
The Tabot tradition in Bengkulu represents a distinctive legacy of Islamic civilization, rooted in the commemoration of the Karbala tragedy introduced by South Indian ulama in the 18th century. Through library research, this study explores Tabot as a manifestation of Islamic-local cultural acculturation imbued with religious, social, and economic values. The findings reveal that Tabot functions not only as a sacred ritual but has also transformed into an inclusive cultural festival that strengthens social cohesion and promotes creative economy through cultural tourism. This transformation underscores Tabot’s role as a medium of character education, a symbol of tolerance, and a marker of Bengkulu’s cultural identity. The literature review also highlights limitations such as risks of over-commodification and tensions among cultural actors. Nevertheless, opportunities remain through educational initiatives, collaborative governance, and digital archiving. Thus, this library-based community engagement contributes to the preservation of local Islamic heritage while providing socio-economic benefits to society.